Bactericidal impact of Ag, ZnO and mixed AgZnO colloidal nanoparticles on H37Rv Mycobacterium tuberculosis phagocytized by THP-1 cell lines. (September 2017) - Jafari, Alireza; Mosavari, Nader; Movahedzadeh, Farahnaz; Nodooshan, Saeedeh Jafari; Safarkar, Roya; Moro, Rossella; Kamalzadeh, Morteza; Majidpour, Ali; Boustanshenas, Mina; Mosavi, Tahereh
Abstract: The purpose of this research project was to infection of human macrophages (THP-1) cell lines by H 37 Rv strain of Mycobacterium tuberculosis ( H 37 RvMTB ) and find out the ratio/dilution of mixture silver (Ag NPs) and zinc oxide nanoparticles (ZnO NPs) whose ability to eliminate phagocytized bacteria compared to rifampicin. The colloidal Ag NPs and ZnO NPs were synthesized and their characteristics were evaluated. The THP-1 cell lines were infected with different concentration of H 37 RvMTB . Next, the infected cells were treated with different ratios/dilutions of Ag NPs, ZnO NPs and rifampicin. The THP-1 were lysed and were cultured in Lowenstein-Jensen agar medium, for eight weeks. The TEM and AFM images of NPs and H 37 RvMTB were supplied. It is observed that Ag NPs, 2Ag :8ZnO and 8Ag :2ZnO did not have any anti-tubercular effects on phagocytized H 37 RvMTB . Conversely, ZnO NPs somehow eliminated 18.7 × 10 4 CFU ml −1 of H 37 RvMTB in concentration of ∼ 0.468 ppm. To compare with 40 ppm of rifampicin, ∼ 0.663 ppm of 5Ag :5ZnO had the ability to kill of H 37 RvMTB, too. Based on previous research, ZnO NPs had strong anti-tubercular impact against H 37 RvMTB to in-vitro condition, but it was toxic in concentration of ∼ 0.468 ppm to both of THP-1 and normal lung (MRC-5) cell lines. It also seems that 5Ag :5ZnO is justified because in concentration of ∼ 0.663 ppm of 5Ag :5ZnO, phagocytized H 37 RvMTB into the THP-1 had died without any toxicity effects against THP-1 and also MRC-5 cell lines. It is obvious that the mixture of colloidal silver and zinc oxide NPs with ratio of 5Ag :5ZnO would be trustworthy options as anti-tubercular nano-drugs in future researches. Highlights: Present research was to study the infection of human macrophages (THP-1) cell lines by H 37 Rv strain of Mycobacterium tuberculosis (H 37 RvMTB ). To determine the ratio/dilution of mixture silver and zinc oxide nanoparticles whose ability to eliminate phagocytized bacteria was compared to rifampicin. The Synthesis of colloidal silver and zinc oxide nanoparticles and their characteristics concurred with other published work. The concentration of ∼ 0.663 ppm of 5Ag :5ZnO, was found to be optimal with no toxicity on THP-1 and MRC-5 cells but successfully eliminated (killed) the phagocytized H 37 RvMTB. The mixture of colloidal AgZnONPs with ratio of 5Ag :5ZnO (∼ 0.663 ppm) may have a great potential as an anti-tubercular nano-drug.